1969
DOI: 10.1039/c29690001447
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the C9–10unit of ajmaline and reserpine

Abstract: Glycine can be a specific precursor of the Cgvl0 unit (I) of ajmaline (11), and probably of reserpine (111), and may be a fundamental precursor for this unit in alkaloids.RECENTLY we reported that glycine could be specifically incorporated into the C,-,, unit as it occurs in the isoquinoline alkaloid cephaeline in Cephaelis acuminata, but that it was a poor precursor of fl-sitosterol in the same plant.lS2 At the same time it was confirmed that while acetic acid acts as a normal precursor of /%sitosterol, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The separation of this mixture faces a technical challenge owing to the formation of a minimum‐boiling azeotrope. Many methods can be used to separate azeotropic mixtures, for example, azeotropic distillation, pressure‐swing distillation, extractive distillation, adsorption, pervaporation using membranes, and some other new separation techniques . Specifically for toluene and pyridine, the present major technologies are pressure‐swing distillation, extractive distillation, and azeotropic distillation, performed in the presence of entrainers .…”
Section: Methodsmentioning
confidence: 99%
“…The separation of this mixture faces a technical challenge owing to the formation of a minimum‐boiling azeotrope. Many methods can be used to separate azeotropic mixtures, for example, azeotropic distillation, pressure‐swing distillation, extractive distillation, adsorption, pervaporation using membranes, and some other new separation techniques . Specifically for toluene and pyridine, the present major technologies are pressure‐swing distillation, extractive distillation, and azeotropic distillation, performed in the presence of entrainers .…”
Section: Methodsmentioning
confidence: 99%
“…The separation of this mixture faces a technical challenge owing to the formation of a minimum-boiling azeotrope. Many methods can be used to separate azeotropic mixtures, for example, azeotropic distillation, [3] pressure-swing distillation, [4] extractive distillation, [5] adsorption, [6] pervaporation using membranes, [7] and some other new separation techniques. [8] Specifically for toluene and pyridine, the present major technologies are pressureswing distillation, extractive distillation, and azeotropic distillation, performed in the presence of entrainers.…”
mentioning
confidence: 99%
“…We wondered whether cucurbit[n]urils crystals had the same behavior as NACs of macrocyclic arenes in addition to their permanently porous form. Herein, we, for the first time, utilized cucurbit- [6]uril (Q [6]) crystals as adsorptive separation materials to achieve the separation of the minimum-boiling azeotrope of toluene/pyridine (Scheme 1). We found that nonporous cucurbit [6]uril crystals (Q[6]a) separated pyridine from toluene with 100 % purity.…”
mentioning
confidence: 99%
See 2 more Smart Citations